Algorithm to Solve Linear Volterra Fractional Integro-Differential Equation via Elzaki Transform - A. Mohammed, Amaal; H. Abd, Yasmin (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, Elzaki transform (ET) introduced by Tarig Elzaki is applied to solve linear Volterra fractional integro-differential equations (LVFIDE). The fractional derivative is considered in the Riemman-Liouville sense. The procedure is based on the application of (ET) to (LVFIDE) and using properties of (ET) and its inverse. Finally, some examples are solved to show that this is computationally efficient and accurate.